Research on key cobalt technologies based on patent analysis - Hua, Zhijing; Dai, Tao (Frontiers in Energy Research, 2023)
Based on global cobalt technology patents, this paper uses patent data mining and co-occurrence methods to identify technology application trends, key technology areas, key technology layouts, and technology roadmap. According to the development trend, the development of co-cobalt technology is divided into slow and rapid development stages. The conclusion are: 1) In terms of key technologies, E35-V (Cobalt compound) is the long-term R&D focus in the field of cobalt, and X16-B01F1 (Lithium-based) is the most important key technology area at present. 2) China, Japan, the United States, and South Korea are the main contributors to key cobalt technologies, mainly focusing on the R&D layout of L03-E01B5B (Lithium electrode) technology in the field of X16-B01F1 (Lithium-based). 3) Regarding the cooperation relationship between patent applicants, cooperation between groups is relatively close, cooperation between different countries is less, and transnational cooperation is mainly concentrated in developed countries, among which the United States has the most transnational partners. 4) In the field of cobalt’s most important electrode material technology LG Chemical Co., Ltd. (Korea) and Sumitomo Metal Mining Corporation (Japan) are the two companies with clear technology lines, while Univ Cent South (China) has a late technology development. Finally, we make suggestions for the development of cobalt technology: focus on core technology for R&D and innovation, actively study the technology status and innovation mode of leading companies, and strengthen the cooperation among different R&D institutions.